Mediation Effect of Resilience on The Relationship Between Self-Efficacy and Competitiveness Among University Students - Kingston K.F. Moke; Calvin K.W. Chang; Kususanto Prihadi; Chee Leong Goh (Institute of Advanced Engineering and Science, 2018)
This study aims to evaluate the mediation role of resilience on the link between self-efficacy and competitiveness among university students in Malaysia. One hundred and thirty-six participants from several universities in Malaysia were recruited to respond to an online form consisted of the following scales: adapted versions of brief resilience scale from Smith et al, self-efficacy scale from Biemann, Kearney and Marggraf, and Personal Development Competitive Attitude Scale from Ryckman, Hammer, Kaczor and Gold. Data was analyzed by using SPSS with PROCESS Macro and full mediation has been observed. Bias-corrected bootstrap confidence interval test indicated that the indirect effect of self-efficacy on competitiveness was significant and the Sobel test had confirmed the significance of the mediation. Further discussion, limitation and suggestion are discussed in the end of the paper.